2010
DOI: 10.1111/j.1471-4159.2009.06491.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasticity‐associated genes regulated by Pavlovian fear conditioning in the lateral amygdala

Abstract: J. Neurochem. (2010) 112, 636–650. Abstract Most recent studies aimed at defining the cellular and molecular mechanisms of Pavlovian fear conditioning have focused on protein kinase signaling pathways and the transcription factor cAMP‐response element binding protein (CREB) that promote fear memory consolidation in the lateral nucleus of the amygdala (LA). Despite this progress, there still remains a paucity of information regarding the genes downstream of CREB that are required for long‐term fear memory forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 63 publications
4
62
0
Order By: Relevance
“…However, Hall and colleagues found equivalent increases in EGR-1 mRNA expression in the LA following exposure to the context alone, suggesting that EGR-1 may not play a selective role in fear learning (Hall et al 2000). This latter pattern of findings is consistent with a recent study that has shown that exposure to a novel context alone can induce robust expression of a variety of genes in the LA (Ploski et al 2010), and suggests that the use of contextual fear conditioning paradigms may be potentially problematic for the study of gene expression following fear learning (Davis et al 2003). In the present series of experiments, we have re-examined the role of EGR-1 in the consolidation of fear memories in the LA using an auditory fear conditioning task.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…However, Hall and colleagues found equivalent increases in EGR-1 mRNA expression in the LA following exposure to the context alone, suggesting that EGR-1 may not play a selective role in fear learning (Hall et al 2000). This latter pattern of findings is consistent with a recent study that has shown that exposure to a novel context alone can induce robust expression of a variety of genes in the LA (Ploski et al 2010), and suggests that the use of contextual fear conditioning paradigms may be potentially problematic for the study of gene expression following fear learning (Davis et al 2003). In the present series of experiments, we have re-examined the role of EGR-1 in the consolidation of fear memories in the LA using an auditory fear conditioning task.…”
Section: Resultssupporting
confidence: 79%
“…In the present series of experiments, we have re-examined the role of EGR-1 in the consolidation of fear memories in the LA using an auditory fear conditioning task. Unlike contextual fear learning tasks, auditory fear conditioning paradigms provide a means to examine training-related changes in gene expression in the absence of those driven by exposure to a novel context (Ploski et al 2010). In our first series of experiments, we asked whether auditory fear conditioning regulates the expression of EGR-1 protein in the LA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…sponse to different chemical stimuli presented above, we collected five studies in which different types of stimulations were used, including LTP and chemical stimulation paradigms, for comparison with our data (Hansen et al, 2008;Lemberger et al, 2008;Jancic et al, 2009;Ploski et al, 2010;Ryan et al, 2011). We found that SRF was associated with LTP, kainate, and cocainemediated stimulation, whereas EGR1 was solely linked with cocaine-mediated induction of gene expression.…”
Section: Meta-analysis Of Activity-driven and Caprtf-dependent Gene Pmentioning
confidence: 99%